Prevalence Profiles of Cryptococcal Antigenemia Among HIV/AIDS Patients Attending Antiretroviral Therapy Clinic at Masaka Regional Referral Hospital, Masaka District in Uganda. A Cross-Sectional Study - Asiimwe, Moses; Mabonga, Habert (SJ Mircobiology Africa, 2024)
Cryptococcosis is an opportunistic infection with Cryptococcus neoformans a fungus that lives in the environment worldwide. The study aimed to determine the Prevalence profiles of Cryptococcal antigenemia among HIV/AIDS patients attending the Antiretroviral Therapy Clinic at Masaka Regional Referral Hospital, Masaka District in Uganda. A cross-sectional study included HIV-positive patients receiving ART who attended the HIV/AIDS clinics at Masaka Regional Referral Hospital – ART Clinic. Blood samples were analyzed for Cryptococcus neoformans and Cryptococcus meningitis antibodies. 45.54% of the respondents were females and 54.46% were males. The majority (85.0%) of participants were aged 15-44. The prevalence of cryptococcal antigenemia was 8.91% (9/101). Prevalence amongst females was 15.2% (7/46) and 3.6% (2/55) amongst males. Males accounted for 22% (2/9) and females accounted for 78% (7/9) of the positive cases identified. The prevalence of cryptococcal antigenemia was higher in females compared to males among participants aged 15-44 years.